2022
DOI: 10.48550/arxiv.2201.12591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermal energy census with the Sunyaev-Zel'dovich effect of DESI galaxy clusters/groups and its implication on the weak lensing power spectrum

Abstract: We carry out a thermal energy census of hot baryons at 𝑧 < 1, by cross-correlating the Planck MILCA y-map with over 40 DESI galaxy cluster/group subsamples constructed from the Yang et. al ( 2021) catalog. In our investigation, we select 0.8 million clusters/groups with richness ≥ 5 and estimated halo mass ≥ 10 13 𝑀 /ℎ. The detection of the thermal Sunyaev-Zel'dovich (tSZ) effect is significant in the investigated clusters/groups. (1) The total measurement S/N of the one-halo term is 65. We constrain the 𝑌 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…For instance, the DESI sample at higher redshifts is weighted towards more massive objects, and hence this measurements conflates the (opposite) effects of redshift evolution and halo mass dependence. Given that we have found a strong dependence of the measured 𝑌 − 𝑀 relation on observational selection and analysis methodology, we leave a more careful comparison to Chen et al (2022)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the DESI sample at higher redshifts is weighted towards more massive objects, and hence this measurements conflates the (opposite) effects of redshift evolution and halo mass dependence. Given that we have found a strong dependence of the measured 𝑌 − 𝑀 relation on observational selection and analysis methodology, we leave a more careful comparison to Chen et al (2022)…”
Section: Discussionmentioning
confidence: 99%
“…Note that their result is mostly from the massive galaxy clusters. Recently, by measuring the stacked tSZ signal around DESI galaxy clusters/groups using the Planck SZ 𝑦-map, Chen et al (2022) found a slightly steeper 𝑌 − 𝑀 slope than the self-similar model, which also has a slight tendency of increase with redshift.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical or best-fit results are presented for Lovisari et al (2015); Eckert et al (2016); Dietrich et al (2019) since these do not provide individual cluster data. Note that other works, such as Lin & Mohr (2004); Gonzalez et al (2007); Andersson et al (2011); Budzynski et al (2014) and also the recent works Lim et al (2020); Chen et al (2022) (estimating gas fractions with SZ signal instead of X-ray) that also examined clusters at 𝑧 ∼ 0.1 to investigate similar fractions, are not included in this comparison due to different reasons, such as no 𝑀 500 or 𝑀 * being available, or that the sample is dominated by 𝑧 0 clusters. However, it has been suggested that there is almost no redshift evolution in both gas and stellar fractions within 𝑧 ∼ 1 (see more discussion below), so we include the best fitting results from the recent work of Akino et al (2021) out to modest redshifts using weak-lensing masses (Umetsu et al 2020) for the 136 XXL clusters in the HSC-SSP survey, shown as the grey shaded band.…”
Section: C1: the Gas And Stellar Fractionsmentioning
confidence: 99%
“…Ref. [72] used thermal Sunyaev-Zeldovich map from Planck around stacked DESI catalog to explore the baryonic feedback. They found β to be always positive, which is consistent with our analysis choice of fixing β = 0.321,; their constraint on M c also agrees with our findings.…”
Section: Comparison With X-ray Data and Previous Workmentioning
confidence: 99%